Einige Bemerkungen zum Infografischen in der visuellen Publizistik - Makowska, Magdalena (Studia Germanica Posnaniensia, 2019)
Infographics has become one the most popular forms used in contemporary communication. It is employed both in traditional media as well as electronic ones in order to present relations between various phenomena or explain particular mechanisms of action in a picturesque way. Infographics is a hybrid form which reaches out for disparate visual elements: linguistic, pictorial and diagram ones, and combines them in a nonlinear way. In media communication infographics occur both as an independent message, or as e.g. an element accompanying a press article and complementing it. The purpose of the article is to demonstrate that infographics as a visual plane can serve the economization and rationalisation of media communication.